Diet intake control is indispensable for the gluconeogenic response to sodium–glucose cotransporter 2 inhibition in male mice - Hashiuchi, Emi (J Diabetes Investig, 2020)
AIMS/INTRODUCTION: Sodium–glucose cotransporter 2 inhibitor (SGLT2i) lowers blood glucose and causes a whole‐body energy deficit by boosting renal glucose excretion, thus affecting glucose and energy metabolism. This energy deficit not only decreases bodyweight, but also increases food intake. This food intake increase offsets the SGLT2i‐induced bodyweight decrease, but the effect of the food intake increase on the SGLT2i regulation of glucose metabolism remains unclear. MATERIALS AND METHODS: We administered SGLT2i (luseogliflozin) for 4 weeks to hepatic gluconeogenic enzyme gene G6pc reporter mice with/without obesity, which were either fed freely or under a 3‐hourly dietary regimen. The effect of feeding condition on the gluconeogenic response to SGLT2i was evaluated by plasma Gaussia luciferase activity, an index of the hepatic gluconeogenic response, in G6pc reporter mice. Energy expenditure was measured by indirect calorimetry. RESULTS: In the lean mice under controlled feeding, SGLT2i decreased bodyweight and plasma glucose, and increased the hepatic gluconeogenic response while decreasing blood insulin. SGLT2i also increased oxygen consumption under controlled feeding. However, free feeding negated all of these effects of SGLT2i. In the obese mice, SGLT2i decreased bodyweight, blood glucose and plasma insulin, ameliorated the upregulated hepatic gluconeogenic response, and increased oxygen consumption under controlled feeding. Under free feeding, although blood glucose was decreased and plasma insulin tended to decrease, the effects of SGLT2i – decreased bodyweight, alleviation of the hepatic gluconeogenic response and increased oxygen consumption – were absent. CONCLUSIONS: Food intake management is crucial for SGLT2i to affect glucose and energy metabolism during type 2 diabetes treatment.